HARMONISASI KONFLIK: INTEGRASI PENDEKATAN ILMU MUKHTALIF AL-HADITS DAN ADAT BADAMAI UNTUK RESOLUSI KONFLIK DALAM HUKUM ISLAM) - Sagir, Akhmad; Monady, Hanief; Hasan, Muhammad; Abdul Majid, Latifah; Abidin, Muhammad Zainal (Universitas Islam Negeri Antasari Banjarmasin, 2023)
This article explores a harmonization approach in conflict resolution by integrating Ilmu Mukhtalif Al-Hadits and Adat Badamai within the framework of Islamic Jurisprudence. Ilmu Mukhtalif Al-Hadits, emphasizing the interpretation of conflicting hadiths, and Adat Badamai, within the context of the Banjar society, employing principles such as musyawarah and mekarajah, are considered aligned approaches in maintaining harmony and justice. The analysis demonstrates similarities in the principles of musyawarah, mekarajah, and decision-making by respected authorities in both approaches, aiming to achieve fair and harmonious agreements. This article highlights the significance of local wisdom, justice, and harmony in conflict resolution, considering consistency with Islamic teachings. In conclusion, the article proposes the integration of Ilmu Mukhtalif Al-Hadits and Adat Badamai as a method to bridge differences in conflict resolution, acknowledging the richness of local values while ensuring conformity with Islamic principles within a broader legal framework.